The suitability of the GERDyzer instrument in pH-test-proven laryngopharyngeal reflux patients. Issue 31 (August 2016) - Wu, Cheng-Pin; Liang, Wen-Miin; Wang, Chen-Chi; Chang, Chi-Sen; Yeh, Hong-Zen; Hsu, Jeng-Yuan; Ko, Chung-Wang; Lee, Shou-Wu; Chang, Shu-Chuan; Sung, Fung-Chang; Lien, Han-Chung
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: The use of validated patient-reported outcome (PRO) instruments for the treatment outcome measure of laryngopharyngeal reflux (LPR) is crucial given the lack of objective markers. However, current symptom-based PRO instruments can only partially capture the impact of LPR. The GERD Analyzer (GERDyzer), an existing disease-specific PRO instrument, which measures multidimensional health-related quality of life (HRQL) affected by the illness rather than by any specific symptoms, has been validated in patients with erosive gastroesophageal reflux disease (GERD). Following the U.S. Food and Drug Administration PRO guidance, we cross-culturally adapted the GERDyzer instrument into Chinese, and examined the qualitative and quantitative psychometric properties of the Chinese version GERDyzer in pH-test-proven LPR patients. The GERDyzer comprises 10 dimensions of HRQL, including general well-being, pain/discomfort, physical health, diet, energy, activities, leisure activities, social life, mood, and sleep. To examine the content validity, we recruited 26 pH-test-proven LPR participants to conduct 4 focus group meetings for direct patient input on clinical manifestations and HRQL impacts. We also tested the quantitative psychometric properties, including reliability, validity, and responsiveness in 100 pH-test-proven LPR patients. Saturation of concept elicitation was achieved from the 4 focus groups, and a strong conceptual match was evident between the GERDyzer contents and responses from the focus group participants. Cognitive debriefing assessment showed that the Chinese version GERDyzer was adequate for use by patients as it demonstrated linguistic validation and cultural harmonization. Quantitative psychometric properties showed evidence of high internal consistency (Cronbach α: 0.96), good to excellent test-retest reliability (intraclass correlation coefficient: 0.84–0.98). Confirmatory factor analysis supported a 2-factor structure. Convergent validity was confirmed by moderate correlation assessments referencing the Reflux Symptoms Index and the Reflux Questionnaire. The discriminant validity was supported by the ability to discriminate moderate-to-severe disease from mild disease. The responsiveness was also high in participants with and without typical GERD symptoms (effect sizes 1.20 and 1.21, respectively). In conclusion, the Chinese version GERDyzer instrument is a reliable, valid, and responsive instrument for assessing HRQL in Taiwanese patients with LPR.